Growth of reproductive organ and its effect on laying performance of medium ype layer due to different levels of dietary protein in growing period - Suprijatna, Edjeng; Natawihardja, Dulatip (Indonesian Journal of Animal and Veterinary Sciences, 2005)
The purpose of this experiment was to study the optimal of dietary protein level of medium type layer in growing period associated with the growth of reproductive organ and the effect on laying performance. The experiment used 480 pullets of 10 weeks old grouped into three treatments of three protein levels, 12, 15 and 18. In laying period all of the treatments used the same ration with 15% protein. The results showed that dietary protein level in growing period significantly affected the growth of reproduction organ, growth performance and eggs quality. Effects of treatment in laying period was significantly different on laying performance only in early laying period, and subsequent period was not differently different. The conclusion of this experiment was the level of 12% adequate for minimal growth, level of 15% adequate for optimal growth and level 18% showed better performances during laying period. The results suggest that in growing period the dietary protein level is not below 15%. Â  Â  Key Words: Protein, Reproduction Organ, Laying Performance